Naphthoquine: An Emerging Candidate for Artemisinin Combination Therapy - Moore, Brioni; Laman, M.; Salman, S.; Batty, Kevin; Page-Sharp, Madhu; Hombhanje, F.; Manning, L.; Davis, T.M.E. (ADIS INT LTD, 2016)
© 2016 Springer International Publishing Switzerland. Naphthoquine is a 4-aminoquinoline antimalarial drug first synthesised in China in 1986 but which was not developed for clinical use until the late 1990s. Early in vitro parasite sensitivity and in vivo efficacy data, together with a long terminal elimination half-life (up to 23 days), suggested that it could be used as monapy for uncomplicated falciparum and vivax malaria, but is now marketed as a single-dose, fixed co-formulation with artemisinin in a milligram per kilogram ratio of 1:2.5. This form of artemisinin combination therapy (ACT) has also shown high cure rates, especially in two randomised trials in which, consistent with World Health Organization recommendations for all ACTs, it was administered daily for 3 days rather than as single dose for Plasmodium falciparum and P. vivax infections (28-day adequate clinical and parasitological response ≥98.4 %). Although detailed safety monitoring has been performed in a minority of subjects, >4000 healthy volunteers and patients with malaria have been exposed to naphthoquine without any documented significant toxicity. As with other 4-aminoquinolines, naphthoquine is associated with prolongation of the electrocardiographic QT interval but not with cardiac or neurological events. It has been administered to children as young as 4 months of age but, due to a lack of pharmacokinetic, efficacy and toxicity data in young infants and in pregnant/lactating women, it should not be used in these vulnerable patient groups.With the emergence of parasite resistance to other ACTs, naphthoquine partnered with a potent artemisinin derivative may prove a viable alternative treatment for uncomplicated malaria.